Frequency of Plasma Leak in Patients with Dengue Fever - Nazir Shah, Mian Mufarih Shah, Sheraz Jamal Khan, Daneeth Kumar, Gul Rukh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the frequency of plasma leak as evident by pleural effusion and ascites in the patients of dengue fever. Study Design: Cross-sectional study. Place and Duration: Medical unit of Hayatabad Medical Complex, Peshawar Pakistan from April 2021 to September 2021. Methodology: Patients diagnosed as having dengue fever based on positive dengue antigen (NS 1) test or antibodies serology on enzyme linked immunosorbent assay (ELISA) were evaluated. Plasma leak was defined as having ascites or pleural effusion evident on ultrasound or X ray chest of the patients with active dengue fever. Hematocrit of >50% in female and 55% in male was considered as indirect indicator of plasma leak. Results: In a total of 154 patients, 89 (57.8%) were male and 65 (42.2%) female with age ranging between 14 to 75 years while mean age was 40.6±15.54 years. The over all frequency of plasma leak as evident by ascites or pleural effusion was 44.2% (n=68. The minimum duration in which plasma leak was noted, remained 4 days while the maximum was 8 days after the start of illness. The duration of patient’s hospital stay was 5 to 17 days (mean 9.53±3.43 days). Practical implications: The frequency of plasma leak was higher in complicated dengue fever patients as compared to patients with less or no complications. Conclusion: Plasma leak is an important and frequent feature of dengue fever. X ray chest and ultrasound can detect majority of plasma leak in patients with hemoconcentration. Keywords: dengue fever, plasma leak, dengue NS1, dengue shock, dengue hemorrhage